A randomized clinical trial of the effects of saphenous and perforating veins radiofrequency ablation on venous ulcer healing (VUERT trial). (April 2021) - Puggina, Juliana; Sincos, Igor Rafael; Campos, Walter; Porta, Rina Maria P; dos Santos, Jorgete Barreto; De Luccia, Nelson; Puech-Leão, Pedro; Collares, Felipe Birchal; da Silva, Erasmo Simão
Objectives: To investigate whether radiofrequency endovenous ablation (RFA) of saphenous and perforating veins increases venous leg ulcer (VLU) healing rates and prevents ulcer recurrence. Method: This prospective, open-label, randomized, controlled, single-center trial recruited 56 patients with VLU divided into: compression alone (CR, N = 29) and RFA plus compression (RF, N = 27). Primary endpoints were ulcer recurrence rate at 12 months; and ulcer healing rates at 6, 12, and 24 weeks. Secondary endpoints were ulcer healing velocity; and Venous Clinical Severity Score (VCSS). Results: Recurrence was lower in the RF group (p < .001), as well as mean VCSS after treatment (p = .001). There were no significant between-group differences in healing rates. Healing velocity was faster in the RF group (p = 0.049). In the RF group, 2 participants had type 1 endovenous heat-induced thrombosis (EHIT). Conclusions: RFA plus compression is an excellent treatment for VLU because of its safety, effectiveness, and impact on ulcer recurrence reduction and clinical outcome. Registration: Clinicaltrials.gov, NCT03293836, clinicaltrials.gov.